Skeleton sled velocity profiles: a novel approach to understand critical aspects of the elite athletes' start phases - Colyer, S. L.; Stokes, K. A.; Bilzon, J. L. J.; Salo, A. I. T. (Sports Biomechanics, 2018)
The development of velocity across the skeleton start is critical to performance, yet poorly understood. We aimed to understand which components of the sled velocity profile determine performance and how physical abilities influence these components. Thirteen welltrained skeleton athletes (>85% of athletes in the country) performed dry-land push-starts alongside countermovement jump and sprint tests at multiple time-points. A magnet encoder attached to the sled wheel provided velocity profiles, which were characterised using novel performance descriptors. Stepwise regression revealed four variables (pre-load velocity, pre-load distance, load effectiveness, velocity drop) to explain 99% variance in performance (â weights: 1.70, -0.81, 0.25, -0.07, respectively). Sprint times and jump ability were associated (r ± 90% CI) with pre-load velocity (-0.70 ± 0.27 and 0.88 ± 0.14, respectively) and distance (-0.48 ± 0.39 and 0.67 ± 0.29, respectively), however, unclear relationships between both physical measures and load effectiveness (0.33 ± 0.44 and -0.35 ± 0.48, respectively) were observed. Athletes should develop accelerative ability to attain higher velocity earlier on the track. Additionally, the loading phase should not be overlooked and may be more influenced by technique than physical factors. Future studies should utilise this novel approach when evaluating skeleton starts or interventions to enhance performance. ABSTRACT FROM AUTHOR